A companion to popular culture - Burns, Gary, 1952 June 10- (Chichester, West Sussex : Wiley Blackwell, 2016)
A Companion to Popular Culture is a landmark survey of contemporary research in popular culture studies that offers a comprehensive and engaging introduction to the field. -Includes over two dozen essays covering the spectrum of popular culture studies from food to folklore and from TV to technology -Features contributions from established and up-and-coming scholars from a range of disciplines -Offers a detailed history of the study of popular culture -Balances new perspectives on the politics of culture with in-depth analysis of topics at the forefront of popular culture studies.
'Includes over two dozen essays covering the spectrum of popular culture studies from food to folklore and from TV to technology'-- Provided by publisher.
Machine generated contents note: Notes on Contributors Introduction 1. Communication, American Studies, Cultural Studies, and Popular Culture Gary Burns POPULAR CULTURE AS A FIELD OF STUDY 2. The Historical Study of Popular Culture George Lipsitz 3. Textual Criticism of Popular Culture Brendan Riley 4. Ethnographic and Folkloristic Study of Popular Culture Daniel Margolies 5. Preservation, Restoration, and Accessibility of Popular Culture Materials Karen Whedbee TEXTS, GENRES, AND FORMULAS 6. The History and Logic of Genre Study Tricia Jenkins 7. Genres and Formulas in Popular Literature and Theatre Gary Hoppenstand 8. Popular Music Genres Marco Katz Montiel 9. Popular Genres in the Visual Arts Joy Sperling MEDIA AND TECHNOLOGIES 10. Technological Determinism Rob Drew 11. Material Culture and Heritage Marilyn Motz 12. Film and Television in Popular Culture Chuck Berg and Ron Wilson 13. Computers and Culture Paul Booth PASTIMES AND PRACTICES 14. Holidays, Festivals, and Foodways Ann Hetzel Gunkel 15. Sports, Tom Oates 16. Circuses, Carnivals, World's Fairs and Expositions, and Theme Parks Kathy Merlock Jackson 17. Humor in Popular Culture Ben Urish 18. Tourism, Travel, and Transportation Max Skidmore USES AND ABUSES 19. Advertising and Consumerism Devon Powers 20. Fashion in Popular Culture Trish Cunningham 21. Popular Religion Nancy Schaefer 22. Children's Popular Culture Angela Sorby 23. Sex and Violence Jane Caputi POLITICS OF CULTURE 24. The Culture Industries Tom Discenna 25. Globalization Mel van Elteren 26. The Politics of Documentary Jeff Chown 27. Culture Jamming and Media Activism Amber Day 28. Who Owns Culture? Heather McIntosh 29. Culture Wars, the Academy, and Future Directions for the Study of Popular Culture Michael Marsden Index .
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Popular culture -- Study and teaching; SOCIAL SCIENCE / Popular Culture; Popular culture -- Study and teaching; Electronic books